Teacher's Efforts In Improving Children's Self-Confidence Through The Role-Playing Method In Group B II At The Muslim Cadani Integrated Islamic Kindergarten In The 2024/2025 Academic Year - Nilatul Aslamiah; Juandra Prisma Mahendra; Rusman Hadi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Researchers found significant problems at the Muslim Madani Islamic Integrated Kindergarten, which could have a negative impact on the children's future. These problems include children lacking confidence to express their feelings, feeling shy in front of large groups of people, and feeling embarrassed to perform in front of others. Therefore, the researchers were interested in investigating whether role-playing methods could enhance the self-confidence of 5-6-year-old children at the Islamic Integrated Muslim Kindergarten Madani for the 2024/2025 academic year. The research method used in this study was Classroom Action Research (CAR) by Kemmis & McTaggart. The results of the study found that this role-playing method is highly effective in enhancing self-confidence in children aged 5-6 years at the Muslim Madani Integrated Islamic Kindergarten. The study results show that in Cycle I, children's self-confidence reached 53.3%, which was followed by Cycle II, in Cycle II, the children's self-confidence increased to 86.6%, meaning that the criteria for significant development were met with a classical percentage of 80% achieved in this study. On average, the children's self-confidence improved, particularly through the role-playing method to enhance self-confidence in Group B2 at the Muslim Madani Integrated Islamic Kindergarten for the 2024/2025 academic year.